AWARENESS AMONGST YOUTH ABOUT USE AND ABUSE OF STEROIDS IN KARACHI, PAKISTAN - Khan, Auwais Ahmed; Ghayas, Sana; Mehtab, Amna; Aaiman, Umm-e-; Idrees, Mehak; Anjum, Fakhsheena (Universal Journal of Pharmaceutical Research, 2018)
Objective: Aim of present study was to analyze awareness regarding the use of steroids in the youth studying health sciences. A descriptive, observational study was conducted from September to December 2017. Youth studying health sciences aged 21–25 years in Karachi were recruited for the study, among which (n=179) 50.99% were pharmacy students and (n=172) 49% were studying allied health sciences. Descriptive statistics (SPSS version 16.0) was used to analyze the results. Methods: Out of 400 questionnaires, the response rate was 87.75%. Majority students were knowledgeable about steroids and (72.64%) agreed that steroids should be sold as prescription only medicine in Pakistan (p= 0.00). Most of them n=147 (41.88%) had no idea about various modes of steroid abuse (p=0.00).Many participants (n= 109;31.05%) thought that steroids were found in toothpaste and dentifrices, cosmetics and ophthalmic preparations; n= 135 (38.46%) had no idea whether or not the steroids had interactions with opiates and cocaine, alcohol and benzodiazepines. Results: The perception was seen in n= 118 (33.61%) persons that nutritional alternative/supplements could be used to reduce steroid abuse; n= 79 (22.50%) used steroids for grooming upon prescription by medical practitioner. Allergic reactions were thought as the mild side effects of steroid use by n= 100 (28.24%) while n= 166 (47.29%) considered kidney and liver diseases as severe side effects of steroid use (p=0.00). Conclusion: It is concluded that comprehensive information about the steroids was required by youth since they were studying health sciences. Some modifications in the curriculum have to be made for providing more information about substances like steroids to the health sciences students as steroids have a great impact not only physically but also psychologically. Peer Review History: Received 23 May 2018; Revised 6 July; Accepted 25 September; Available online 15 September 2018 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Antonio José de Jesus Evangelista , Federal University of Ceará, UFC, Brazil, tony_biomed@hotmail.com Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com